Community Forums to Address Vaccine Hesitancy: A Useful Tool for Meeting the Needs of Diverse Communities - Laura Palombi; Jazmin Belknap; Mary Jo Katras; Grant Anderson (University of Minnesota Libraries Publishing, 2023)
Community forums are a valuable tool in engaging rural communities to address critical public health issues. Recognizing low levels of COVID-19 vaccine uptake in rural Minnesota communities and the critical public health threat that resulted, pharmacy faculty and Extension professionals from the University of Minnesota partnered with a diverse group of rural stakeholders to plan a series of six community forums to provide life-saving, evidence-based education about the COVID-19 vaccine. Each forum allowed trusted local community leaders, public health workers and healthcare providers to share information about the impact of COVID-19 in their communities.  Data about the COVID-19 vaccines was provided, and community members were allowed to ask questions and voice their concerns about the virus and the vaccines. Virtual community forums allowed rural stakeholders to reach a diverse and geographically remote population while maintaining COVID-19 distancing requirements. Offering a safe, virtual space and immediate access to reliable and trusted place-based education allowed individuals an opportunity to get their vaccine questions answered immediately. Community forums can be conducted in rural communities as a direct communication tool to address critical public health issues such as vaccine hesitancy, and empower community members to make informed decisions in fighting against the COVID-19 pandemic.